Academic Remediation–Focused Alternative Schools: Impact on Student Outcomes. (March 2016) - Wilkerson, Kimber L.; Afacan, Kemal; Yan, Min-Chi; Justin, Whitney; Datar, Sujata D.
School districts offer specialized programming for secondary students who experience high rates of course failure or low credit accumulation. While these alternative programs are meant to increase student success, little research evaluates outcomes for students attending them. In this study, we used propensity score matching (PSM) to investigate the effectiveness of secondary alternative schools on four student outcomes: school attendance, credits earned, number of office referrals, and number of suspensions. Findings from Poisson regression analyses indicate that attending an academic remediation–focused alternative school is associated with significantly lower attendance but also with earning significantly more credits than enrollment in a traditional school. In addition, enrollment in an alternative school is associated with significantly less office referrals and suspensions than enrollment in a traditional school. Implications for policy, practice, and further research are discussed.